The Role of Pesantren Wahdah Islamiyah in Providing Character Education Programs at Insan Rabbani Integrated Islamic Elementary School, Malili, Indonesia - Sudarsono, Sudarsono; Muchtar, Asmaji; Warsiyah, Warsiyah (Universitas Muhammadiyah Yogyakarta, 2025)
This study aims to examine the role of Pesantren Wahdah Islamiyah Luwu Timur in providing and implementing character-building programs at the Integrated Islamic Elementary School (SDIT) Insan Rabbani Malili. The research focuses primarily on the forms of collaboration between the pesantren and the school, the types of moral development programs implemented, and their impact on students' character formation. A qualitative research approach was employed, utilizing data collection techniques such as observation, in-depth interviews, and documentation. The findings indicated that Pesantren Wahdah Islamiyah played a strategic role as an active partner in moral education, particularly in curriculum development, teaching personnel, and regular religious activities such as halaqah (study circles), mentoring, and the cultivation of daily worship habits. These programs have positively contributed to developing students’ character, especially in discipline, responsibility, and social ethics. This study addresses a gap in the literature where limited research explores the direct, structured collaboration between pesantren and formal Islamic schools at the elementary level. Its novelty highlights the pesantren’s multi-dimensional role—conceptual, operational, and implementational—in shaping character education within a formal school context, offering a practical model for integrated Islamic education.